Exploring emotional intelligence and mood states variations in combat sports athletes: insights from sport modality, gender, and training experience (Revista de Artes Marciales Asiáticas, 2026)
Recent studies suggest that combat sports which require athletes to adapt high-pressure situations and manage their emotions may enhance emotional intelligence (EI) and influence mood states. The present study examined the EI and mood states among combat sports athletes according to sport modality, gender and training experience. A total of 226 athletes from grappling (judo, wrestling) and striking (taekwondo, karate, boxing) disciplines completed the Arabic emotional intelligence scale (A-EIS) and the Arabic Mood Scale (ARAMS). Results indicated that striking athletes demonstrated higher EI and more positive mood profiles than grappling athletes. Male athletes showed greater EI and more favorable mood states compared to females. In addition, greater training experience was associated with higher emotional intelligence and positive mood dimensions. The study findings highlight the role of sport type, gender, and experience in shaping athletes’ emotional and psychological profiles, suggesting that emotional skills and mood regulation may be enhanced through training and experience in combat sports.